Exploring Strategic Management Based on Islamic Values in Pesantren-based Higher Education - Purnomo, Muhammad Sidiq; Mulyadi, Mulyadi; Slamet, Slamet (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research analyzes strategic management based on Islamic values at Islamic boarding school-based universities in East Java Province. Through a cross-case qualitative approach, this research analyzes the strategic formulation, implementation, and evaluation stages and their implications for improving the quality of education. Interviews, observations, and documentation were conducted to obtain accurate and valid data. Data analysis uses the Miles and Huberman interactive model: data collection, data presentation, data condensation, and drawing conclusions. The results of this research show that the strategic planning process needs to be carried out through deliberation with core stakeholders and HR (human resources) involved in higher education institutions and the need to develop Islamic values in the strategic planning process, namely istiqamah (continuously), da'wah (inviting people to join), ittihad (unity), mashlahah (general goodness), ihtiyat (prudence). These Islamic values were developed to optimize strategic planning components: scanning, establishing a vision, mission, tag lines, policies, and strategies. These several components form a unit that cannot be separated in the strategic planning process in responding to the future challenges of educational institutions.